Comparison of Lower Secondary School Education of Mathematics in the Czech Republic and Selected Countries with Respect to Curriculum Documents - Moravcová, Vlasta; Surynková, Petra; Hromadová, Jana (Scientia in educatione, 2019)
Results from the PISA international surveys in 2012 and 2015 show that the performance of Czech pupils in mathematics was statistically comparable with the OECD average. However, in the long-term comparison, the results appear to have statistically worsened in the Czech Republic. The PISA score of other European countries with similar economies in terms of GDP and common historical-cultural development, namely Estonia, Poland, and Slovenia, was higher or even significantly higher. The search for the causes of this leads, among other things, to the study of the mathematics curricula of these states. Our paper gives a brief overview of the education systems of the selected countries, while also conducting a qualitative comparative analysis of relevant curriculum documents for lower secondary education. We place emphasis on the differences between the Czech curriculum and the curricula of the other countries. This is explored with the overall aim of formulating educational objectives pertaining to mathematics learning, the subject matter and its division, and required learning outcomes. In the last chapter we present the most significant differences (the lowest number of mathematics lessons, the absence of general mathematical goals and competencies, the lack of emphasis on home preparation of pupils, the absence of unified testing and insufficiently detailed learning content and outcomes), which could be an inspiration for improving the Czech mathematics curriculum.